Nilai Pendidikan Agama Hindu Dalam Lontar Swargarohana Parwa - I Nyoman Ariyoga (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2019)
The Indonesian people, especially the Hindu community, have their own local wisdom which is an indigenous culture that has been passed down through generations. One of the local wisdoms of the Hindu community is the story found in the lontar text. The teachings of Hinduism are abundant in lontar texts in the form of Babad, Tantri and in the epics of the Mahabharata and Ramayana. In the concept of the story there are many teachings of Hinduism education which can directly be applied in living life in this world. Thus the authors are interested in writing more broadly about the stories in Lontar Swargarohana Parwa contained in the Mahabharata. Lontar Swargarohana Parwa is the last eighteenth part of the Mahabharata. This story is about Yudistira reaching heaven, but he chose to live in hell with his brothers and wife instead of living in heaven with the Korawa and Sekuni, but a few moments later the situation turned to hell and vice versa. In Lontar Swargarohana Parwa there are a lot of Hindu religious education values ​​contained in it, so this paper was carried out to review Lontar Swargarohana Parwa viewed from a study of Hindu religious education. Keywords: Hindu Religious Education, Lontar Swargarohana Parwa